Incidence of the sampling depth on the content of forms of carbon and nitrogen in soils of the Zona Bananera of the department of Magdalena (Colombia) (2022)
The objective of the work was to determine the incidence of the sampling depth on the carbon and nitrogen content in soils of the municipality of Zona Bananera of the department of Magdalena (Colombia). Data analysis was performed with statistical software Infostat v.2008 and R v.3.5.2, using multivariate analysis of variance, Pearson's correlation analysis, and descriptive statistics of each variable. The results show significant differences (p<0,05) between the depth groups for the selected variables, with lower contents found at depth 2. In addition, there is a significant contribution of the variables to the statistical differences between the groups, except for ammonium and nitrate. Correlation is evident between the variables C oxidizable/MO, NO3-/NO2-, and NH4+/C oxidizable/MO. The results obtained showed low Pearson correlation coefficients. It is concluded that the variables C oxidizable and MO are strongly related, while the others present a non-linear relationship.